2010
DOI: 10.1186/1756-3305-3-85
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Anopheles gambiae s.l (Diptera: Culicidae) exhibiting different vectorial capacities in lymphatic filariasis transmission in the Gomoa district, Ghana

Abstract: BackgroundTwo lymphatic filariasis endemic communities Mampong and Hwida in Ghana have been regularly monitored for impact on transmission after annual mass drug administration (MDA) with albendazole and ivermectin. After six MDAs even though the ABR for Mampong was 55883/person/year and that of Hwida was 2494/person/year, they both had ATPs of 15.21 infective larvae/person/year. Interestingly the human microfilaraemia levels had reduced significantly from 14% to 0% at Mampong and 12% to 3% at Hwida. In an att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 17 publications
1
25
0
1
Order By: Relevance
“…Because limitation of An. gambiae ( sensu stricto ) has been observed in Ghana [31], it should also be assessed in other geographic locations (e.g. Mali) given the possibility of adaptation or specific mutation that can modify mosquito’s transmission pattern [32].…”
Section: Discussionmentioning
confidence: 99%
“…Because limitation of An. gambiae ( sensu stricto ) has been observed in Ghana [31], it should also be assessed in other geographic locations (e.g. Mali) given the possibility of adaptation or specific mutation that can modify mosquito’s transmission pattern [32].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the Polynesian Islands of Moorea and Maupiti, where the vector was Aedes polynesiensis, over 50 years of MDA using DEC did not eliminate LF [17]. Despite these evidences and the assumption of vector-parasite phenomenon of Facilitation in Anopheles , there is current growing evidence that in certain areas, Anopheles species may be exhibiting the process of Limitation [26,27]. …”
Section: Reviewmentioning
confidence: 99%
“…melas compared to the M and S forms of the An. gambiae s.s [27]. As such, it is very clear from the above that anopheline LF vectors in West Africa may differ in their capacity to sustain low-level microfilaraemia.…”
Section: Reviewmentioning
confidence: 99%
“…Other studies have also found sympatric species of the An. gambiae complex and M and S molecular forms [34], [35] to have different competency to transmit W. bancrofti . Further research on the vector competence of primary LF vectors around the world, in the context of a diminishing mf reservoir, is needed in order to maximize the success of the Global Programme to Eliminate Lymphatic Filariasis.…”
Section: Discussionmentioning
confidence: 99%